The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/jo2013466
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-Promoted Addition of 1,3-Bis(silyl)propenes to Aldehydes: A Route to 1,3-Dienes

Abstract: The Lewis acid-promoted addition of 1,3-bis(silyl)propenes to aldehydes to provide the corresponding (E)-1,3-dienes in excellent stereoselectivity and good to excellent yields is reported. The procedure is mild, base-free, and operationally straightforward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The stereoisomerically pure alcohols 4f-h were transformed into both the (E)-and (Z)-dienes 1 by similar treatment with acid or base with complete stereoselectivity (entries 5-10). 15 The trisubstituted butadienes 1f and g were also obtained with high stereoselectivity by the treatment of highly substituted b-hydroxy silanes 4i and k (entries [11][12][13][14].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereoisomerically pure alcohols 4f-h were transformed into both the (E)-and (Z)-dienes 1 by similar treatment with acid or base with complete stereoselectivity (entries 5-10). 15 The trisubstituted butadienes 1f and g were also obtained with high stereoselectivity by the treatment of highly substituted b-hydroxy silanes 4i and k (entries [11][12][13][14].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Somfai and co-workers reported the preparation of (E)-1-monosubstituted 1,3-dienes by the Lewis acid-promoted reaction of 1,3-bis(silyl)propenes with aldehydes. 13 However, the application of this method to the preparation of (Z)-1,3-dienes or more highly substituted congeners has not appeared yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the Nozaki–Hiyama16 allylation of aldehydes, followed by a Peterson‐type olefination protocol17 has been used in the total synthesis of a number of natural products that contain a 1,3‐dienic moiety 18. More recently, the stereoselective synthesis of ( E )‐1,3‐dienes by a Lewis‐acid‐promoted addition of 1,3‐bis(silyl)propenes to aldehydes has been described in the literature 19. On the other hand, the reaction of aldehydes with N ‐allylhydrazine derivatives gives 1,3‐dienes with high levels of E stereoselectivity, but this approach is limited to aromatic aldehydes 20.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Various groups have reported the synthesis of 1,3-dienes through a Peterson olefination starting from 1,3-bis(trimethylsilyl)propene (Scheme 2a). [27][28][29][30][31] Deprotonation with organolithium bases, in combination with diamine or phosphoramide additives, and addition into carbonyl compounds produces 1,3-diene products in one step, albeit in low yields and poor stereoselectivity. 27,28 Chan and coworkers found that the addition of MgBr2 to the organometallic reagent enabled the isolation of the β-hydroxysilane intermediate, which could be treated under acidic or basic conditions to stereoselectively form (1E, 3E)-or (1E, 3Z)dienes.…”
mentioning
confidence: 99%